Case of Treatment of Solid Pseudopapillary Pancreatic Tumor - F. S. Rakhimova; N. D. Mamashev; O. A. Shimkina; B. Kh. Bebezov (Креативная хирургия и онкология)
Introduction. A solid pseudopapillary pancreatic tumor accounts for less than 3 % of all pancreatic tumors. It is more common in young women aged 20 to 30. The prognosis for this pathology is favorable. Complete removal of the tumor leads to full recovery in more than 85 % of patients.   Materials and methods. The paper presents a clinical case which demonstrates the surgical outcome of a patient with a malignant pancreatic tumor. Patient M., female, born in 1998, underwent inpatient treatment at the I.K. Akhunbaev Clinic of National Hospital, Kyrgyzstan, from January 12, 2015 to January 26, 2015 with a clinical diagnosis — pancreatic head mass, which was found intraoperatively. Due to this, the decision was made to expand the scope of the surgery. Histopathological examination revealed a solid pseudopapillary tumor.   Results and discussion. This tumor is extremely rare and is usually detected accidentally during preventive examinations, or when the tumor becomes large. Against the background of treatment, the dynamics of observation for 7 years revealed no signs of progression and relapse of this pathology.   Conclusion. Solid pseudopapillary tumor is a rare, highly differentiated malignancy, which develops most oft en in young women. It is characterized by a relatively favorable clinical course, which is demonstrated by this case report.